Renegades eaudiobook - Meyer, Marissa (Renegades, 2017)
"Both narrators bring authenticity to the young characters...this fun and surprisingly thoughtful superhero tale will be a rewarding listen." — AudioFile Magazine From #1 New York Times -bestselling author Marissa Meyer, comes a high-stakes world of adventure, passion, danger, and betrayal. This new audiobook will pull listeners in and never let them go... Secret Identities. Extraordinary Powers. She wants vengeance. He wants justice. The Renegades are a syndicate of prodigies—humans with extraordinary abilities—who emerged from the ruins of a crumbled society and established peace and order where chaos reigned. As champions of justice, they remain a symbol of hope and courage to everyone...except the villains they once overthrew. Nova has a reason to hate the Renegades, and she is on a mission for vengeance. As she gets closer to her target, she meets Adrian, a Renegade boy who believes in justice—and in Nova. But Nova's allegiance is to a villain who has the power to end them both. Renegades is the next hit YA audiobook listeners have been waiting for!